2018
DOI: 10.1093/geronb/gby024
|View full text |Cite
|
Sign up to set email alerts
|

Aging and n-Back Performance: A Meta-Analysis

Abstract: Objectives: To provide a systematic review of age-related differences in n-back performance. Method: Meta-analytic data aggregation. Results: Access for items stored within the focus of attention (0-back and 1-back) was very fast and quasi-perfect; when items are held outside the focus (n > 1), an additional cost was accrued in both accuracy and response time. Age-related differences in accuracy conformed to this bifurcation. Longer lists led to larger costs when going from 1-back to 2-back in older adults. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 74 publications
6
67
0
Order By: Relevance
“…If the only constraint on performance is imposed by the limited-capacity of individual components of the working memory system, which titration is assumed to correct for, older adults should be able store at least 2-3 items at a time. Bopp and Verhaeghen's (2018) finding that age-related differences remained stable over values of n from 2-back onwards, suggests that the constraint is not working memory load per se, but rather the involvement of focus switching processes. Thus, it appears that titration does play a role in reducing age differences, but the theoretical insight this reduction provides into the functional underpinnings of working memory remains unclear.…”
Section: Discussionmentioning
confidence: 93%
“…If the only constraint on performance is imposed by the limited-capacity of individual components of the working memory system, which titration is assumed to correct for, older adults should be able store at least 2-3 items at a time. Bopp and Verhaeghen's (2018) finding that age-related differences remained stable over values of n from 2-back onwards, suggests that the constraint is not working memory load per se, but rather the involvement of focus switching processes. Thus, it appears that titration does play a role in reducing age differences, but the theoretical insight this reduction provides into the functional underpinnings of working memory remains unclear.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the 0-back, 1-back, and 2-back tests were administered. The 0-back test is essentially a memory search task of sustained attention and often used as a control condition (Miller et al, 2009;Bopp and Verhaeghen, 2018). The 1-back test requires the participant to passively store and update information in working memory.…”
Section: N-back Testmentioning
confidence: 99%
“…Older age is associated with reduced working memory capacity in general (cf. Bopp and Verhaeghen, 2018 for a recent meta-analysis). More specifically, it has been repeatedly demonstrated that the aging-related deficit in working memory is larger for item manipulation than for item maintenance (e.g., Li et al, 2008 ) and that maintenance of items in working memory is relatively spared in old age unless the amount of distraction or working memory load are increased (e.g., Gazzaley et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“… Owen et al, 2005 for meta-analysis) and age-related differences in working memory performance ( Kirchner, 1958 ; cf. Bopp and Verhaeghen, 2018 ) is the n -back task. In line with the theoretical framework of multiple-embedded components of working memory ( Cowan, 2001 ; Oberauer, 2002 ; Oberauer and Hein, 2012 ), previous research has shown that the necessity of switching attentional focus with increasing n -back load reduces the n -back performance level more strongly in older compared to younger adults, but with different effects on the accuracy and speed of working memory: With increasing n -back load age differences in accuracy increase, whereas age differences in response time seem to remain relatively stable (e.g., Dobbs and Rule, 1989 ; Verhaeghen and Basak, 2005 ; Vaughan et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%